Pemanfaatan Arsip Data Laboratorium Dalam Analisis Perbedaan Kadar Bilirubin Direk Pada Individu Dengan Riwayat Konsumsi Alkohol - Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
Laboratory data archives represent an essential form of dynamic records that support scientific accountability and healthcare decision-making. This study aims to analyze differences in direct bilirubin levels among individuals with and without a history of alcohol consumption based on laboratory data archives. The research employed an analytical observational method with a cross-sectional approach supported by archival data analysis. The data were obtained from laboratory examination records and respondent information. The results showed that individuals with a history of alcohol consumption had higher direct bilirubin levels compared to non-consumers. From an archival perspective, properly managed laboratory records enable systematic, accurate, and traceable data analysis. However, inconsistencies in documentation may affect data quality. This study highlights the importance of strengthening laboratory archival systems to ensure reliable health data and support evidence-based decision-making.